The Palgrave Handbook of Race and the Arts in Education (Springer International Publishing, 2018)
The Palgrave Handbook of Race and the Arts in Education is the first edited volume to examine how race operates in and through the arts in education. Until now, no single source has brought together such an expansive and interdisciplinary collection in exploration of the ways in which music, visual art, theater, dance, and popular culture intertwine with racist ideologies and race-making. Drawing on Critical Race Theory, contributing authors bring an international perspective to questions of racism and anti-racist interventions in the arts in education. The book's introduction provides a guiding framework for understanding the arts as white property in schools, museums, and informal education spaces. Each section is organized thematically around historical, discursive, empirical, and personal dimensions of the arts in education. This handbook is essential reading for students, educators, artists, and researchers across the fields of visual and performing arts education, educational foundations, multicultural education, and curriculum and instruction.